Pengembangan Jaringan Metro Ethernet Menggunakan Metode Qinq Di PT.Aplikanusa Lintasarta - Roni Sunjaya (AMMA : Jurnal Pengabdian Masyarakat, 2025)
In the current era of digitalization, data communication is very important, to support data communication needs, of course, a network is needed that is able to make data communication easy and able to reach all corners of the world. PT. Aplikanusa Lintasarta is one of the providers that provides Metro Ethernet network services to support data communication for its customers. One of the Metro Ethernet networks managed by PT. Aplikanusa Lintasarta is the network for GTT Communications, Inc. This study aims to develop a Metro Ethernet network that connects the location of DCI Bekasi with Sigma Sentul. Currently customers are in need of increasing the number of VLANs and want to add VLANs without the need to add or change VLANs on the provider side, for that the Metro Ethernet network development process is carried out using the QinQ method to overcome this problem. In its implementation, the development of the Metro Ethernet network focuses on the configuration process at each distribution switch port, both on the DCI Bekasi side and on the Sigma Sentul side. After the configuration is complete, it is continued with network testing based on the QOS (Quality of Service) parameters, the result is that networks using QinQ have a lower packet loss value of 0% compared to networks that do not use QinQ with a value of 0.006%, so for network latency using QinQ more stable with a latency value of 5ms, while a Metro Ethernet network that does not use QinQ has a higher latency value of 26ms.